Comparison of the Effects of Carperitide and Tolvaptan on Patients with Left Ventricular Dysfunction: A Two-Center Retrospective Study. (12th July 2017) - Koeda, Chikahiko; Yamaya, Shohei; Hozawa, Maiko; Sato, Masayuki; Nasu, Kazuhiro; Takahashi, Tomohiro; Terui, Katsutoshi
Abstract : In patients with left ventricular (LV) dysfunction, diuretics can reduce blood pressure and lead to electrolyte abnormalities. The aim of this study was to compare the effects of tolvaptan (T group) and carperitide (C group) in these patients. Sixty-one consecutive patients admitted to the Iwate Prefectural Kuji Hospital or the Emergency Center of the Iwate Medical University between July 2011 and April 2015 were included in this study. These patients had acute heart failure (HF) and were initially treated with furosemide. Patients were excluded from the study if they received combined carperitide and tolvaptan, if they received tolvaptan or cardiotonic drugs prior to the study period, if their LV ejection fraction was ≥40%, and if they had renal dysfunction (serum creatinine > 2.0 mg/dL). There were no differences in the change in serum electrolytes in both groups, and none of the patients in the T group received supplementary dobutamine therapy. Oxygen administration was stopped successfully after a significantly shorter treatment period in the T group. These findings suggest that patients treated with tolvaptan did not require dobutamine as frequently as those treated with carperitide and indicated that tolvaptan may improve respiratory function more rapidly in patients with LV dysfunction.